Language planning and national identity in Croatia - Langston, Keith (Palgrave studies in minority languages and communities, 2014)
Following the collapse of the former Yugoslavia, Croatian was declared officially to be a separate language, distinct from Serbian, and linguistic issues became highly politicized. This book examines the changing status and norms of the Croatian language and its relationship to Croatian national identity. It focuses on the period following the creation of an independent Croatian state in 1991, but encompasses broader historical developments to provide a context for understanding the contemporary linguistic situation. The complex history of language standardization in the Yugoslav lands and the emphasis on language planning in Croatia make this an especially interesting case study that offers insight into wider debates about linguistic identity, language policy, and language planning issues in general.